Advances in real-time systems - Eberspacher, Jorg; Chakraborty, Samarjit (Springer Berlin Heidelberg, 2012)
This volume has been prepared in honor of Prof. Georg Färber, to celebrate his 34 years of service at TU München, as the Head of the Lehrstuhl für Realzeit-Computersysteme. It contains a collection of articles reflecting the state-of-the-art in the area of real-time systems. The topics included span over automotive software and electronics, software timing analysis, models for real-time systems, compilation of real-time programs, real-time microkernels and cyber-physical systems. It is intended to serve as a reference book for graduate-level courses. It will also be helpful to both researchers in the academia, as well as to practitioners from the industry.